Business and human quality (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This contribution starts with a discussion of the notion of human quality, specially underlining its relationship with values and its distinction from the notions of sensitivity and spirituality. Once the notion is clarified in terms that go some what beyond the standard understanding of the term, its possible incidence in the corporate field is analyzed, with special attention to four fields: the reliability of personal work, the facilitation of team work, the promotion of creativity and the generation of corporate cohesion. It also refers to the relationship between human quality andpersonal motivation, as well as its inclusion as criteria in the configuration and operationof professional teams.
Keywords: Human quality; sensitivity; spirituality; values; motivation.